Leitura da evolução da forma urbana do Plateau - Cidade da Praia - Cortês, F.; Genin, S.; Sampaio, M. T. de. (Book of proceedings ICEUBI 2019, International Congress on Engineering University da Beira Interior “Engineering for Evolution", 2019)
An analysis of urban morphology of the historical nucleus (the Plateau) of Praia (Cape Verde) highlights the process of thinking and making a city expressed in António de Lencastre 's plan and its further development. For this, the processes of urban transformation occurring over time in the Plateau are shown. The methodology used for this urban analysis allowed an understanding of the intervention process on the Plateau through an interpretative analysis of morphological evolution obtained from: i) a detailed identification of cartography; ii) a comparative morphological analysis of urban development based on old and current cartography; iii) a vectorization of the maps through scale normalization (the letters were overlapped with the 2018 chart); iv) an identification of public buildings and public spaces; and v) a quantification of the elements of urban form. In the quantification of the elements of the urban form, the reading and interpretation of the different maps is synthesized through analytical drawings and tables.